Risks to healthcare workers following tracheal intubation of patients with COVID‐19: a prospective international multicentre cohort study. (9th July 2020) - El‐Boghdadly, K.; Wong, D. J. N.; Owen, R.; Neuman, M. D.; Pocock, S.; Carlisle, J. B.; Johnstone, C.; Andruszkiewicz, P.; Baker, P. A.; Biccard, B. M.; Bryson, G. L.; Chan, M. T. V.; et al.
Summary: Healthcare workers involved in aerosol‐generating procedures, such as tracheal intubation, may be at elevated risk of acquiring COVID‐19. However, the magnitude of this risk is unknown. We conducted a prospective international multicentre cohort study recruiting healthcare workers participating in tracheal intubation of patients with suspected or confirmed COVID‐19. Information on tracheal intubation episodes, personal protective equipment use and subsequent provider health status was collected via self‐reporting. The primary endpoint was the incidence of laboratory‐confirmed COVID‐19 diagnosis or new symptoms requiring self‐isolation or hospitalisation after a tracheal intubation episode. Cox regression analysis examined associations between the primary endpoint and healthcare worker characteristics, procedure‐related factors and personal protective equipment use. Between 23 March and 2 June 2020, 1718 healthcare workers from 503 hospitals in 17 countries reported 5148 tracheal intubation episodes. The overall incidence of the primary endpoint was 10.7% over a median (IQR [range]) follow‐up of 32 (18–48 [0–116]) days. The cumulative incidence within 7, 14 and 21 days of the first tracheal intubation episode was 3.6%, 6.1% and 8.5%, respectively. The risk of the primary endpoint varied by country and was higher in women, but was not associated with other factors. Around 1 in 10 healthcare workers involved in tracheal intubation of patients with suspected or confirmed COVID‐19 subsequently reported a COVID‐19 outcome. This has human resource implications for institutional capacity to deliver essential healthcare services, and wider societal implications for COVID‐19 transmission. 요약: 기관 삽관과 같은 에어로졸을 생성하는 시술에 관여하는 의 료 종사자는 COVID‐19에 걸릴 위험이 높아질 수 있다. 그러 나 그 위험의 크기는 알려져 있지 않다. 저자들은 COVID‐19 가 의심되거나 확인된 환자의 기관 삽관에 참여한 의료 종사 자를 모집하는 전향적 국제 다기관 코호트 연구를 수행하였 다. 기관 삽관 에피소드, 개인 보호장비 사용 및 이후 시술자 건강 상태에 대한 정보를 자가 보고(self‐reporting)를 통해 수집하였다. 일차 평가변수는 기관 삽관 후 자가 격리 또는 입 원이 필요한 검사실 확인 COVID‐19 진단(laboratory‐con‐ firmed COVID‐19 diagnosis) 또는 새로운 증상의 발현이었 다. 일차 평가변수와 의료 종사자 특성, 시술 관련 요인 및 개 인 보호장비 사용과의 연관성을 콕스 회귀분석(Cox regres‐ sion analysis)을 이용하여 조사하였다. 2020년 3월 23일부터 6월 2일까지 17개국의 503개 병원에서 1718명의 의료 종사자 들이 기관 삽관 에피소드 5148건을 보고하였다. 일차 평가변 수의 전체 발생률은 32일의 중앙값(사분범위[범위]: 18‐48일 [0‐116일]) 추적관찰 동안 10.7%였다. 첫 번째 기관 삽관 이후, 7일, 14일, 21일 이내 누적 발생률은 각각 3.6%, 6.1%, 8.5%였 다. 일차 평가변수의 위험은 국가별로 다양하였으며 여성에서 더 높았지만, 다른 요인과는 관련이 없었다. COVID‐19가 의심 되거나 확인된 환자의 기관 삽관에 관여한 의료 종사자 10명 중 약 1명은 후속적으로 COVID‐19 결과를 보고하였다. 이는 필수적인 의료 서비스를 제공할 수 있는 기관 역량에 대한 인 적 자원 측면의 영향과 COVID‐19 전파에 대한 더욱 광범위한 사회적 영향을 미친다.